Asuhan Keperawatan Keluarga Pada KeluargaDengan Gout Arthritis Di Wilayah Kerja Puskesmas Pariaman Kota Pariaman - Elza Mayang Sari; Armaita Armaita; Hasmita Hasmita; Sandra Dewi (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
According to the World Health Organization, the prevalence of gout arthritis worldwide continues to increase each year, with an incidence ranging from 1%–4% in the general population. It is more common in men than women, especially in Western countries, with a prevalence of around 3%–6%, and in individuals over 80 years old it can reach 10% in men and 6% in women. Gout arthritis is a joint inflammation caused by the accumulation of uric acid crystals due to purine metabolism disorders. If not managed promptly and appropriately, it can lead to joint damage, tophi formation, heart disease, kidney stones, and reduced quality of life. This case study aims to apply family nursing care to a family with gout arthritis. The method used is the nursing process, including assessment, diagnosis, planning, implementation, and evaluation with a descriptive design. Data were collected through interviews, observations, and physical examinations. The results showed that the family experienced joint pain and a lack of knowledge. Three nursing diagnoses were identified: chronic pain, ineffective health management, and deficient knowledge. After 9 days of intervention including health education, pain management, and family involvement, there was a reduction in pain and an improvement in the family’s knowledge and ability to provide care. Family nursing care for patients with gout arthritis was effective in improving knowledge, reducing pain, and enhancing family independence in care through education and the application of a healthy lifestyle.